2022
DOI: 10.7717/peerj.13630
|View full text |Cite
|
Sign up to set email alerts
|

Short physical performance battery as a predictor of mortality in community-dwelling older adults: a longitudinal study in the Brazilian Amazon region

Abstract: Background The Short Physical Performance Battery (SPPB) is an instrument for assessing physical performance widely used in research among the elderly in multiple settings. We did not find Brazilian longitudinal studies that aimed to analyze the predictive capacity and accuracy of the SPPB among community-dwelling older adults and no systematic reviews were found on the accuracy of the SPPB in predicting mortality in community- dwelling older adults. This study aimed to analyze the capacity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…A total of 11,713 articles were screened, and finally, 15 (Araujo, et al, 2022; Blain et al, 2010; Cao et al, 2021; Cesari et al, 2008; Cesari et al, 2009; Idland et al, 2013; Keevil et al, 2018; Ma et al, 2018; Molari et al, 2021; Nofuji et al, 2016; Panas et al, 2013; Rolland et al, 2006; Silva et al, 2022; Takata et al, 2007; Takata et al, 2012) were included in the analysis (15 for qualitative analysis and 14 for quantitative analysis) (Figure 1). Table 1 provides a detailed enumeration of the characteristics of the individual studies that were included for evidence synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 11,713 articles were screened, and finally, 15 (Araujo, et al, 2022; Blain et al, 2010; Cao et al, 2021; Cesari et al, 2008; Cesari et al, 2009; Idland et al, 2013; Keevil et al, 2018; Ma et al, 2018; Molari et al, 2021; Nofuji et al, 2016; Panas et al, 2013; Rolland et al, 2006; Silva et al, 2022; Takata et al, 2007; Takata et al, 2012) were included in the analysis (15 for qualitative analysis and 14 for quantitative analysis) (Figure 1). Table 1 provides a detailed enumeration of the characteristics of the individual studies that were included for evidence synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…(b) Forest plot showing the pooled HR of the association between an inability to perform a balance test and mortality including studies that reported unadjusted HRs. For the Silva et al, 2022 study, the upper boundary of the 95% confidence interval of HR was approximated to the nearest decimal.
Figure 3.(a) Contour-enhanced funnel plot indicating the presence of publication bias including studies reporting adjusted HRs. (b) Bubble plot including studies reporting adjusted HRs showed that the association with mortality was correlated with progressive age.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total SPPB score will be the sum of the scores from all three tests, ranging from 0 to 12. Participants will be classified as having poor (0–3), low (4–6), moderate (7–9), or good (10–12) physical capacity based on their total score [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…The SPPB consists of three sequential tests that assess semi-tandem and tandem balance test, gait speed, and 5-sit-to-stand test. The total score ranges from 0 to 12 points, and 12 showing the best physical function performance to 0 showing inability to do the tests (26). All these physical performance tests were performed before a dialysis session.…”
Section: Evaluation Of Physical Performancementioning
confidence: 99%